Unique Unfoldase/Aggregase Activity of a Molecular Chaperone Hsp33 in its Holding-Inactive State - Jo, Ku Sung; Kim, Ji Hun; Ryu, Kyoung Seok; Kang, Joo Seong; Wang, Chae Yeon; Lee, Yoo Sup; Seo, Min Duk; Lee, Young Ho; Won, Hyung Sik (Journal of Molecular Biology, 2019)
The various chaperone activities of heat shock proteins contribute to ensuring cellular proteostasis. Here, we demonstrate the non-canonical unfoldase activity as an inherent functionality of the prokaryotic molecular chaperone, Hsp33. Hsp33 was originally identified as a holding chaperone that is post-translationally activated by oxidation. However, in this study, we verified that the holding-inactive reduced form of Hsp33 (RHsp33) strongly bound to the translational elongation factor, EF-Tu. This interaction was critically mediated by the redox-switch domain of RHsp33 and the guanine nucleotide-binding domain of EF-Tu. The bound RHsp33, without undergoing any conformational change, catalyzed the EF-Tu aggregation by evoking the aberrant folding of EF-Tu to expose hydrophobic surfaces. Consequently, the oligomers/aggregates of EF-Tu, but not its functional monomeric form, were highly susceptible to proteolytic degradation by Lon protease. These findings present a unique example of an ATP-independent molecular chaperone with distinctive dual functions—as an unfoldase/aggregase and as a holding chaperone—depending on the redox status. It is also suggested that the unusual unfoldase/aggregase activity of RHsp33 can contribute to cellular proteostasis by dysregulating EF-Tu under heat-stressed conditions.
Keywords: Binding Sites; Escherichia coli; Escherichia coli Proteins; Heat-Shock Proteins; Molecular Chaperones; Oxidation-Reduction; Peptide Elongation Factor Tu; Protein Conformation; Protein Folding; Protein Interaction Domains and Motifs; Protein Processing, Post-Translational; Proteolysis; protein aggregation; protein misfolding; protein quality control; protein turnover; proteostasis